2011
DOI: 10.1111/j.1365-2796.2011.02467.x
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of autoimmune conditions following routine use of quadrivalent human papillomavirus vaccine

Abstract: Objective. An observational safety study of the quadrivalent human papillomavirus vaccine (HPV4) in women was conducted. This report presents findings from autoimmune surveillance. Design. Subjects were followed for 180 days after each HPV4 dose for new diagnoses of 16 prespecified autoimmune conditions. Setting. Two managed care organizations in California. Outcome. Potential new-onset autoimmune condition cases amongst HPV4 recipients were identified by electronic medical records. Medical records of those wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
127
4
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(143 citation statements)
references
References 16 publications
7
127
4
5
Order By: Relevance
“…exposure to environmental toxins). The timing of the onset of symptoms, consistency or plausibility of symptoms with the known pharmacology and toxicology of the qHPV, and whether or not an alternative trigger was present were all considered [18][19][20]. Finally, all serious AEFIs were assessed for unexpectedness.…”
Section: Outcome Definitions and Ascertainmentmentioning
confidence: 99%
“…exposure to environmental toxins). The timing of the onset of symptoms, consistency or plausibility of symptoms with the known pharmacology and toxicology of the qHPV, and whether or not an alternative trigger was present were all considered [18][19][20]. Finally, all serious AEFIs were assessed for unexpectedness.…”
Section: Outcome Definitions and Ascertainmentmentioning
confidence: 99%
“…Data have shown that prophylactic HPV vaccination is generally safe and well tolerated. [32][33][34][35][36][37][38] The median age of sexual debut is in the late teens (15-19 years) in most countries. 39 Virginal adolescents (#15 years old) were not included in HPV vaccine efficacy evaluations because of low HPV exposure and ethical constraints.…”
Section: What This Study Addsmentioning
confidence: 99%
“…I read with great interest the article by Chao et al [1] regarding the lack of autoimmune diseases in patients who were vaccinated against HPV. I would like to comment on this report and in particular on the validity of the results and conclusions.…”
mentioning
confidence: 99%
“…the development of multiple sclerosis 3 years after vaccination with either Gardasil or a hepatitis B vaccine) [1,[5][6][7][8].…”
mentioning
confidence: 99%